High frequency current distribution in a structure with application to lightning protection systems - Swanson, Andrew Graham (My University, 2008)
In concrete reinforced buildings, the steel framework is required to be bonded and is often used as a cost effective method of lightning protection. In defining lightning protection zones, it is essential to understand where the lightning current due to a direct strike will flow. A number of models exist to evaluate the current distribution, but are often applied to relatively simple structures. Using Maxwell’s equations, an approximate skin effect model is proposed and used to eval- uate the lightning current distribution in a complex structure. A reduced scale model of a structure, consisting of conductors arranged in rings, is developed to verify the model. Particular attention is given to the return path of the current, ensuring an even distrib- ution of the current in the structure. The equivalent circuit showed an even distribution of current across each conductor at dc and low frequencies and a distribution that concentrated in the outer conductors for higher frequencies. The measurements from the structure confirmed that the current con- centrates in the outer conductors at high frequencies. Applying a reduced scale lightning impulse, it is shown that the majority of the current flows on the outermost conductors. Any current on the inner conductors is not only greatly decreased in magnitude, but significantly slower in time than the applied impulse.
Keywords: lightning protection; lightning current